Mimikrija kao simbolička slika svijeta - Medarić, Magdalena (Array, 2003)
The phenomenon of mimicry, i. e. live beings imitating something they are not, is not attractive only to exact, natural sciences but also to humanistic sciences. Among other theoreticians of culture, mimicry was studied as a kind of a world picture by: N. Evreinov, P. Uspenskij, R. Caillois, J. Lacan. They define mimicry as any imitation, and are interested in the visual aspect and the duality of it. Mimicry as a metaphor or a symbolic picture of the world as struggle for survival.